A cavernous hemangioma in the small intestine of a teenage boy: a case report and literature review - Xie, Tian; Long, Yi (Frontiers in Pediatrics, 2025)
BackgroundA cavernous hemangioma in the small intestine is rare. Due to its hidden location and non-specific clinical symptoms, it is difficult to diagnose accurately. Here, we describe a 14-year-old boy with a cavernous hemangioma and bleeding at the junction of the jejunum and ileum.Case summaryThe patient presented with clinical manifestations including melena, dizziness, fatigue, pale complexion, and shock. Abdominal contrast-enhanced computed tomography identified a hyperdense lesion within the small bowel lumen. Digital subtraction angiography (DSA) revealed aneurysmal changes in the mid-to-lower abdominal branches of the ileojejunal artery, which were suggestive of a hemorrhage originating from a small intestinal hemangioma. However, subsequent DSA-guided interventional embolization failed to achieve hemostasis. Following a hospital-wide multidisciplinary consultation, a laparoscopic exploration was conducted. During the procedure, a 1.5 cm × 1.5 cm mass was detected at the ileojejunal junction and successfully resected. The postoperative pathological examination confirmed the lesion to be a cavernous hemangioma. One week after surgery, the patient's hemoglobin level increased to 86 g/L, with no recurrence of bloody stools. At the 1-month follow-up, no signs of disease recurrence were observed.ConclusionThis case report presents significant clinical implications for the diagnosis and management of small intestinal cavernous hemangiomas in the pediatric population.